Sexual dimorphism in an animal model of Sjögren's syndrome: a potential role for Th17 cells - Voigt, Alexandria (Biol Open, 2015)
Sjögren's syndrome is a complex autoimmune disease with an array of diverse immunological, genetic and environmental etiologies, making identification of the precise autoimmune mechanism difficult to define. One of the most distinctive aspects of Sjögren's syndrome is the high sexual dimorphism with women affected 10-20 times more than men. It is nearly impossible to study the sexual dimorphic development of Sjögren's syndrome in human patients; therefore it is pertinent to develop an appropriate animal model which resembles human disease. The data indicated that female C57BL/6.NOD-Aec1Aec2 mice developed an earlier onset of sialadenitis with a higher composition of CD3(+) T cells and a 10-fold increase in glandular infiltration of Th17 cells at the onset of clinical disease compared to male mice. Inflammatory Th17 cells of female mice exhibited a stronger proliferation in response to disease-specific antigen than their male counterpart. At the clinical disease stage, altered autoantibody patterns can be detected in females whereas they are seldom observed in male C57BL/6.NOD-Aec1Aec2 mice. Interestingly, male C57BL/6.NOD-Aec1Aec2 mice developed an earlier loss of secretory function, despite the fact that female C57BL/6.NOD-Aec1Aec2 mice exhibited a more rapid secretory loss. This data indicates the strong sexual dimorphism in the SjS-susceptible C57BL/6.NOD-Aec1Aec2 animal model, making it an appropriate animal model to examine human disease.